Q‐switched laser depigmentation in vitiligo, most effective in active disease. (December 2013) - Komen, L.; Zwertbroek, L.; Burger, S.J.; van der, J.P.W.; de, M.A.; Wolkerstorfer, A.
Summary Background In widespread vitiligo, when repigmentation therapies are no longer feasible, Q‐switched lasers can be used to remove the remaining disfiguring pigmentation. However, little literature is available on the long‐term effects of Q‐switched laser treatment in patients with vitiligo, and the variables influencing the effect of treatment are unknown. Objective To evaluate retrospectively the effectiveness, safety and patient satisfaction of Q‐switched ruby (QSR) laser‐induced depigmentation in widespread vitiligo. Methods We performed a retrospective study on well‐documented patients with vitiligo with widespread lesions who received depigmentation therapy with the QSR laser between 2000 and 2012 in our institute. Eligible patients were asked to visit our institute for assessment of depigmentation and to fill in a questionnaire on patient satisfaction and disease variables. Results After a mean follow‐up of 13 months, 48% of the 27 included patients showed > 75% depigmentation. Patients with active disease at the time of treatment had significantly better results than patients with stable disease (P < 0·05). Twenty‐three (85%) patients were satisfied after treatment. Eighteen patients (67%) reported temporary side‐effects after treatment. None of the patients reported adverse effects, such as scars or infections. Conclusion Q‐switched ruby laser therapy is effective in approximately half of patients treated; it is a safe treatment with a high patient satisfaction. Patients with active vitiligo show better results after treatment than patients with stable vitiligo. Therefore, in patients with stable vitiligo resistant to trial treatment, we advise postponing treatment until their vitiligo becomes active.